Buried - Plante, Lynda La (New York, New York Zaffre, 2020)
DC Jack Warr and his girlfriend Maggie have just moved to London to start a new life together. Warr is drawn into an investigation that turns his life upside down. In the aftermath of a fire at an isolated cottage, a badly burned body is discovered, as well as the burnt remains of millions of stolen, untraceable bank notes. The search leads Warr deep into a murky underworld.
"Introducing Detective Jack Warr"--Cover
112589
Keywords: Police -- Fiction; Murder -- Investigation -- Fiction; Children of criminals -- Fiction; Adoptees -- Fiction; Detective and mystery fiction; Fiction